Risk in Stream and Royalty Financing of Infrastructure Development - Carmichael, David G.; Edmonson, Craig G. (Universitas Indonesia, 2015)
Stream financing and royalty financing are relatively new ways of enabling the development of infrastructure in the resources sector and provide risk sharing between the parties involved (financing company and resource company), different to other financing methods. The paper explores the peculiarities of stream and royalty financing, and presents a straightforward method, via moments, of assessing the risk associated with the parties losing/gaining money. Analysis variables are characterized by expected values and variances, the latter being used to incorporate any uncertainty or variability. The method assists in understanding the sensitivity of the risk to changes in the underlying terms of the financing agreements and underlying variables. It permits the selection of preferred financing dependent on the risk attitudes of the parties. A case example study is given demonstrating the calculations involved, along with some commentary on non-financial risk issues.